-4t-4=-7t-4

Simple and best practice solution for -4t-4=-7t-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4t-4=-7t-4 equation:


Simplifying
-4t + -4 = -7t + -4

Reorder the terms:
-4 + -4t = -7t + -4

Reorder the terms:
-4 + -4t = -4 + -7t

Add '4' to each side of the equation.
-4 + 4 + -4t = -4 + 4 + -7t

Combine like terms: -4 + 4 = 0
0 + -4t = -4 + 4 + -7t
-4t = -4 + 4 + -7t

Combine like terms: -4 + 4 = 0
-4t = 0 + -7t
-4t = -7t

Solving
-4t = -7t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '7t' to each side of the equation.
-4t + 7t = -7t + 7t

Combine like terms: -4t + 7t = 3t
3t = -7t + 7t

Combine like terms: -7t + 7t = 0
3t = 0

Divide each side by '3'.
t = 0

Simplifying
t = 0

See similar equations:

| (d^2-d+5)-(-d^2+d+5)= | | 120=2a-(15-7a) | | 2w-10=2w+10 | | 12p+7=-17 | | 4(3x-8)-4=4(x-3)+32 | | 3p+1=13 | | 8(3a-52)-4(2a+3)=12 | | -9n-10=-100 | | 12x+11=14x+1 | | 17t+15=11t+51 | | 6y-15=-5y+18 | | (4n-1)(2n+4)= | | 4y+4=3y-6 | | 8x+3=13+3x | | (5a^2x+3ax^2-5x)+(2a^2x-5ax^2+7x)= | | 12x-10=62 | | -5(X+3)2(x-1)=-14 | | 8(2)+5= | | -9w-19=4w-6 | | -9-(4)(2)(x)=3249 | | 8x^2-21x+10=0 | | 8x^2-1x-9=0 | | 10w+16=10w+16 | | 3.2q-4.1-4.6q=-2.4q-3.2 | | 1+p+5+p=-2 | | 6r(2r-1)= | | 5x+24=12x+60 | | 6m+10=25-m | | 5x+11=12x+60 | | (5x^2-x-7)+(2x^2+3x+4)= | | 20e+50f=8(40) | | 22x-26x=10-14 |

Equations solver categories